(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
In the process of Labor, people entering into Reciprocity Act within a certain rule, norm. The attitude of Labor, which is significant for society, is usually strengthened through the law. various regulatory aspects of the relationship find their character at the level of this network, God, organization, enterprise Department, individual employee. The head of the Personal management is obliged to know such regulatory documents, be able to apply them in practice, develop independent drawings on their basis, publicize them, be able to explain to the employees of the organization, their content.